Revitalization of Brownfields in Russian and Baltic Cities: Comparing Interaction Models between Stakeholders in Development Projects - Nekrasova Ekaterina (Lodz University of Technology Press, 2023)
The post-socialist countries since the 1990s had to face both the transformational crisis towards free-market economy and the deindustrialization. It was accompanied by a large-scale closure of inefficient industries and resulted in a significant number of brownfields. Planning redevelopment projects of such post-industrial areas can be manifested in various forms of interaction between stakeholders. However, there has not been sufficient research that would attempt to identify models of stakeholder interaction in the planning stage of brownfield redevelopment projects. This paper is aimed at identifying and comparing stakeholder interaction models at the planning stage of redevelopment projects of former urban industrial areas in post-socialist countries, namely in Latvian, Lithuanian, Estonian and Russian cities. It is accomplished by comparing redevelopment contexts in these countries, and then exploring redevelopment cases of industrial territories in Baltic and Russian cities. Qualitative comparative analysis is based on case comparison by the ownership structure, redevelopment initiators, number of participating stakeholders, their type based on their involvement in the project, and funding model. Based on that, general approaches to the redevelopment of post-industrial areas and specific models of stakeholder interaction in the Baltic and Russian cities are identified and compared.
Keywords: revitalization; brownfields; post-industrial territories; redevelopment projects; stakeholder interaction; rewitalizacja; tereny zdegradowane; tereny poprzemysłowe; projekty przebudowy; interakcja z interesariuszami